2017
DOI: 10.1167/iovs.16-20680
|View full text |Cite
|
Sign up to set email alerts
|

Recurrence of Retinopathy of Prematurity After Intravitreal Ranibizumab Monotherapy: Timing and Risk Factors

Abstract: Recurrence of type 1 ROP should be carefully watched in a long-term follow-up after IVR monotherapy, particularly in the first 12 weeks after IVR and for those with extensive retinal neovascularization or prolonged oxygen therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
44
1
3

Year Published

2018
2018
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 50 publications
(51 citation statements)
references
References 29 publications
(62 reference statements)
3
44
1
3
Order By: Relevance
“…It is noteworthy that peripheral avascularity and fibrosis after primary IVR at an advanced PMA is a major indication for further ROP management. No ROP recurrence was observed in the study, which is different from previous studies of infants treated at an earlier PMA that showed a substantial rate of ROP recurrence after single IVR [18, 19]. Since physiologic vascularization may slow down at an advanced PMA, it is reasonable to anticipate less recurrent neovascularization, but more peripheral avascularity and fibrogenesis after a single anti-VEGF therapy [6].…”
Section: Discussioncontrasting
confidence: 75%
“…It is noteworthy that peripheral avascularity and fibrosis after primary IVR at an advanced PMA is a major indication for further ROP management. No ROP recurrence was observed in the study, which is different from previous studies of infants treated at an earlier PMA that showed a substantial rate of ROP recurrence after single IVR [18, 19]. Since physiologic vascularization may slow down at an advanced PMA, it is reasonable to anticipate less recurrent neovascularization, but more peripheral avascularity and fibrogenesis after a single anti-VEGF therapy [6].…”
Section: Discussioncontrasting
confidence: 75%
“…Ranibizumab use is increasing due to systemic safety concerns (discussed below), but appears to have a higher rate of reactivation, ranging from 26% to 64% for ROP in general, not APROP. [2627282930313233] Moreover, Chuluunbat found an 18% rate of nonresponsiveness. [32] The lack of efficacy may be related to shorter half-life and therefore early reactivation.…”
Section: Discussionmentioning
confidence: 99%
“…[33] However, the effect of anti-VEGF may be transient and there are increasing number of reports of late recurrences with anti-VEGF monotherapy. [343536] The present study included eyes with laser monotherapy only and combination with anti-VEGF could have potentially altered the outcome in some of the cases with zone 1 ROP. Posterior zone I ROP has been shown to have very poor outcome with laser alone and a combination treatment with anti-VEGF may be a better option in such eyes.…”
Section: Discussionmentioning
confidence: 99%